Day-night variations in sleep and locomotor activity in lambs during the first 72 hours after birth and following the onset of rumination - Younes Beniaich; Hicham Farsi; Manal Larbaoui; Hiba Ouardirhi; Nouha Sbai; Mohammed Piro; Mohamed Rachid Achaâban; Paul Pévet; Etienne Challet; Amal Satté; Khalid El Allali (PLoS ONE, 2026)
The sleep-wake and rest-activity profiles of many species undergoes changes during the development. In ruminants, the onset of rumination-related digestive function is contingent on the attainment of full forestomach maturity. The study aimed to characterise sleep–wake at birth and to assess the rumination onset effects on vigilance-states and rest–activity patterns in lambs. Eight newborn lambs were subjected to two non-invasive polysomnographic (PSG) and behavioural recordings. The first recording was conducted immediately after birth for a duration of 72 h, while the second was performed after rumination onset (1–1.5 months) for an additional 72 h. At birth, lambs exhibited twilight activity, with a peak occurrence during the day-night transitions, resulting in an average of 5.3 ± 0.3 h of daytime activity. Following the onset of rumination, a rise in daytime activity was observed, reaching an average of 7.8 ± 0.3 h. PSG results revealed polyphasic sleep, with lambs spending 58.6% (6.4 h) of the night and 39.6% (4.9 h) of the day asleep. The prevalence of NREM-sleep was observed to exceed that of drowsiness and REM-sleep, both during diurnal and nocturnal periods. Four to six weeks later, rumination occupied 28.6 ± 4.5% of the night and 13.3 ± 2.4% of the day, coinciding with reduced sleep time (from 11.3 h to 6.9 h) due to fewer episodes, without changes in episode duration. All sleep stages were found to be affected, whereas wakefulness remained unchanged. These findings suggest that in neonatal ruminants, rumination may compete with sleep without altering wakefulness, providing new insight into behavioural and vigilance states from suckling to the onset of rumination.